Chasing River : a novel - Tucker, K. A. (Kathleen A.), 1978- (Atria Paperback, an imprint of Simon & Schuster, Inc., 2015)
"Armed with two years' worth of savings and the need to experience life outside the bubble of her Oregon small town, twenty-five-year old Amber Welles is prepared for anything. Except dying in Dublin. Had it not been for the bravery of a stranger, she might have. But he takes off before she has the chance to offer her gratitude. Twenty-four-year-old River Delaney is rattled. No one was supposed to get hurt. But then that American tourist showed up. He couldn't let her die, but he also can't be identified at the scene--so, he fled. Back to his everyday life of running his family's pub. Only, everyday life is getting more and more complicated, thanks to his brother, Aengus, and his criminal associations. When the American girl tracks River down, he quickly realizes how much he likes her, how wrong she is for him. And how dangerous it is to have her around. Pushing her away would be the smart move. Maybe it's because he saved her life, or maybe it's because he's completely different from everything she's left behind, but Amber finds herself chasing after River Delaney. Amber isn't the kind of girl to chase after anyone. And River isn't the kind of guy she'd want to catch" --